Community development: an analysis of the programme in India - Bhattacharya, S. N. (Calcutta, 1970)
The book written by one who has been, from the very insep tion of the programme, associated closely with it, attempts an analysis of the programme as it progressed from year to year. It gives a na rrative account of the growth and establishment of 'Panchayati Raj' or local self-goverment. It also shows the need and impor tance of co-operative movement to make community develop ment a success. The programme is now at cross roads in the sense that all its concentration and ac tivities have been focussed at the most important need of the hour -food production-in the face of increasing population.
Keywords: Community Development